Cartographic cinema - Conley, Tom (University of Minnesota Press, 2007)
Maps and movies tell their viewers where they are situated, what they are doing, and, to a strong degree, who they are. In this groundbreaking work, eminent scholar Tom Conley establishes the ideological power of maps in classic, contemporary, and avant-garde cinema to shape the imaginary and mediated relations we hold with the world.